Remote Limb Ischemic Postconditioning Protects against Ischemic Stroke via Modulating Microglia/Macrophage Polarization in Mice - Dong Han; Jue Wang; Lulu Wen; Miao Sun; Hang Liu; Yan Gao (Journal of Immunology Research)
Aim. The protection against ischemia/reperfusion injury mediated by remote limb ischemic postconditioning (RIPC) shows great clinical value in ischemic stroke therapy, but the particular mechanism of RIPC remains unclear. Methods. We carried out middle cerebral artery occlusion/reperfusion (MCAO/R) surgery on C57BL/6 male mice. RIPC was generated by 10-minute occlusion followed by the same period of reperfusion of the bilateral hind limb femoral artery and repeated for 3 cycles. Infarct size and neurological score were performed to assess stroke outcomes. Ly6Chi monocytes were quantified in the blood and brain by flow cytometry. Real-time PCR, ELISA, and immunofluorescence were utilized to detect phenotype of proinflammatory M1 and anti-inflammatory M2 microglia/macrophage. Nuclear factor κB (NF-κB) and peroxisome proliferator-activated receptor γ (PPARγ) levels were detected using Western blot. Results. At 24 and 72 h after MCAO, RIPC drastically attenuated infarct size and ameliorated the neurological deficits of mice and facilitated transmigration of Ly6Chi monocytes to the brain postischemia reperfusion. Furthermore, RIPC contributed to increased M2 and reduced M1 microglia/macrophage through inhibiting NF-κB and promoting PPARγ activation. Conclusion. Our results reveal pharmacological effect of RIPC in promoting microglia/macrophage transferring from M1 to M2 phenotype after MCAO/R in mice, which provides theoretical support for the therapeutic effect of RIPC in ischemic stroke.